VALIDASI METODE ANALISIS SPEKTROFOTOMETRI UNTUK PENETAPAN KADAR FORMALDEHID DALAM IKAN ASIN DENGAN PEREAKSI ASAM KROMOTROPAT - Indriasari, Christina (Widya Warta, 2021)
Formaldehyde is in the form of clear dilution, uncolored or nearly uncolored, pungent, and the vapor stimulates the mucous membranes of the nose and throat as well as stimulates the release of tears. If it is frozen, it becomes turbid. Formaldehyde has an ability as a disinfectant but it is often misused as a preservative of food, such as salted fish. This research aimed to validate the simple, selective, and sensitive spectrophotometry analysis method to determine the total amount of formaldehyde in the sample of salted fish with chromotropic acid reagent. The three types of the salted fish were Jambal, Peda, and Squid samples, in the preparation tested for validation according to linearity, accuracy, and precision. The validation parameter with analysis method obtained linear regression curve Y = 0,0361 + 0,0,0964x (r = 0,9982). The accuracy based on the percent recovery price (% recovery) was 96,04%, and the precision value with the obtained variation coefficient value was 0,0076 Â± 1,83%. The total amount of formaldehyde excreted was within the range of 10,85 ppm to 68,20 ppm.